Comprehensive Analyses of miRNAs Revealed miR-92b-3p, miR-182-5p and miR-183-5p as Potential Novel Biomarkers in Melanoma-Derived Extracellular Vesicles - Gerloff, Dennis; Kewitz-Hempel, Stefanie; Hause, Gerd; Ehrenreich, Jovine; Golle, Linda; Kingreen, Tim; Sunderkötter, Cord (Frontiers in Oncology, 2022)
Extracellular vesicles (EVs) are important mediators in the intercellular communication, influencing the function and phenotype of different cell types within the tumor micro-milieu and thus promote tumor progression. Since EVs safely transport packages of proteins, lipids and also nucleic acids such as miRNAs, EVs and their cargo can serve as diagnostic and prognostic markers. Therefore, the aim of this study was to investigate EV embedded miRNAs specific for melanoma, which could serve as potential biomarkers. In contrast to previous studies, we not only analysed miRNAs from EVs, but also included the miRNA profiles from the EV-secreting cells to identify candidates as suitable biomarkers. While the characterization of EVs derived from normal melanocytes and melanoma cells showed largely comparable properties with regard to size distribution and expression of protein markers, the NGS analyses yielded marked differences for several miRNAs. While miRNA load of EVs derived from normal human epidermal melanocytes (NHEMs) and melanoma cells were very similar, they were highly different from their secreting cells. By comprehensive analyses, six miRNAs were identified to be enriched in both melanoma cells and melanoma cell-derived EVs. Of those, the accumulation of miR-92b-3p, miR-182-5p and miR-183-5p in EVs could be validated in vitro. By functional network generation and pathway enrichment analysis we revealed an association with different tumor entities and signaling pathways contributing melanoma progression. Furthermore, we found that miR-92b-3p, miR-182-5p and miR-183-5p were also enriched in EVs derived from serum of melanoma patients. Our results support the hypothesis that miRNAs derived from EVs can serve as prognostic or diagnostic liquid biopsy markers in melanoma. We identified EV-derived miRNAs and showed that those miRNAs, which were enriched in melanoma cells and EVs, are also found elevated in serum-derived EVs of patients with metastatic melanoma, but not in healthy subjects.